(untitled) (Educação e Pesquisa, 2024)
The purpose of this study is to analyze the most suitable research designs and evaluation instruments for the analysis of training needs in dual training (DT) professionals, assessing the procedures and dimensions that are examined. The figure of the company tutors in DT is an agent key for the preparation of apprentices training in the workplace, which is why it is considered of great interest to determine their needs to improve their professional practice. The methodology used has been the systematic bibliographic review. Starting from the search with a Boolean operator, we obtained 2.470 open access records published. The exploration was limited to the period comprehended between 2011-2021, in six data bases, which contained full text, and peer-reviewed journals and PhD dissertations. Finally, 54 investigations were selected. The findings reflect that the needs studies mostly use mixed research designs in which they apply the combination of interviews (structured, semi structured, in- depth, in group and individual) and questionnaires (online and in-person) as the main instruments of data colleccion. The questionnaires are used, in the majority of cases, to reach as many people as possible in the shortest time and interviews to deepen the subject of study. Regarding the evaluable dimensions, these focus in the methodological and technological aspects, communications and psycho-social skills and development of the own profession.